2003
DOI: 10.1189/jlb.0403157
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytokine profile of human skin mast cells from two compartments—strong resemblance with monocytes at baseline but induction of IL-5 by IL-4 priming

Abstract: Although known as heterogenous, mast cells (MC) are believed to induce allergic inflammation, partially by secretion of T helper cell type 2 (Th2) cytokines. We show here that MC purified from two human skin compartments produce cytokines that are primarily associated with inflammation and innate immunity [interleukin (IL)-1beta, IL-6, IL-8, tumor necrosis factor alpha (TNF-alpha)]. Although these are detectable even without stimulation, immunoglobulin (Ig)E receptor cross-linking is able to enhance only TNF-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 45 publications
4
57
1
Order By: Relevance
“…This is a huge increment as compared to the much lower (and donor-dependent) release observed in skMCs upon purification. 10,13) In the long-term culture model, histamine release triggered by Fc"RI crosslinking reaches the same level as obtained with the calcium ionophore A23187, a well-known non-immunological MC secretagog (Fig. 2B).…”
Section: 2)supporting
confidence: 69%
See 2 more Smart Citations
“…This is a huge increment as compared to the much lower (and donor-dependent) release observed in skMCs upon purification. 10,13) In the long-term culture model, histamine release triggered by Fc"RI crosslinking reaches the same level as obtained with the calcium ionophore A23187, a well-known non-immunological MC secretagog (Fig. 2B).…”
Section: 2)supporting
confidence: 69%
“…Having established a technique to purify MCs to homogeneity from human skin, we have observed that IL-4 prolongs the survival of skin-derived MCs (skMCs). 8,10) It is unknown, however, whether IL-4 can promote skMC proliferation, and whether IL-4 treated skMCs increase in responsiveness towards Fc"RI aggregation, as found for several types of MCs. 6,11) The expression level and function of Fc"RI in skMCs from different human subjects are highly variable, and on average only about 15-25% of histamine is released upon Fc"RI cross-linking in freshly purified skMCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last years IL-4 has been recognized as an important regulator of human mast cells derived from intestine, lung, skin, or cord blood (5)(6)(7)(8)(9)(10)(11). In synergy with SCF, IL-4 enhances proliferation, mediator release, and Th2 cytokine generation.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells were isolated from human breast skin (13)(14)(15) and cultured (in SCF + IL-4) for up to 16 weeks; at defined times, cells were analysed for proliferation (BrdU incorporation), gene expression (quantitative RT-PCR), protein expression (flow cytometry), protease activity, histamine content and stimulation by FceRI-cross-linking. All experimental procedures are detailed in the Supporting Information.…”
Section: Experimental Designmentioning
confidence: 99%